Liturgia «semper reformanda» (latin for «the liturgical is always to be reformed»). The nowadays of a conventional adage - Díez Valladares, SSS, Lino Emilio (Razón y fe, 2018)
The first and the most positively adopted constitution of the Council was the one on the sacred liturgy (Sacrosanctum Concilium). Although the constitution did not have full acceptance, over time it has been, and remains today, one of the most acceptance constitutions. As the author says, this minority but deeply rooted acceptance was not due to external changes but to the fact that today people have trouble with «living the liturgy as a primary spiritual purpose».